Pelatihan Deteksi Dini Terserang Stroke Dengan Metode Fast Pada Lansia Di Kelurahan Sari Bunga Mas Kecamatan Lahat : Training on Early Detection of Stroke Using Fast Methods for the Elderly in Sari Bunga Mas Village, Lahat District - Kamesyworo, Kamesyworo; Haryanti, Eka; Hartati, Sri; Elviani, Yeni (Jurnal Abdi Keperawatan dan Kedokteran, 2024)
Stroke is a common degenerative disease in the elderly, which causes a decrease in quality of life because the elderly become dependent on various daily activities. The fatal and permanent effects of a stroke can be prevented if the patient receives prompt and appropriate medical care within 3-5 hours, known as the "golden period." During this period, stroke disease can be overcome faster and the prognosis becomes better. One way to increase public knowledge about the early symptoms of stroke is through health education. This Community Service activity aims to provide an understanding of the FAST method as an effort to detect stroke early in the pre-hospital environment, especially in the family. The activity methods include pre-test, lectures, demonstrations, leaflets, and post-tests. This activity was attended by 24 cadres and the community of Sari Bunga Mas Village. From the results of data analysis, before the intervention was implemented, there were 12.5% of participants who had good knowledge. After the intervention, the number increased to 79.2%, while the rest had sufficient knowledge.  The results of this activity show that cadre members and the community are able to understand and demonstrate the FAST method for early detection of stroke in the family and community environment well.